Genome-wide association for smoking cessation success: participants in the Patch in Practice trial of nicotine replacement. - Uhl, G; Drgon, T; Johnson, C; Walther, D; David, S; Aveyard, P; Murphy, M; Johnstone, E; Munafò, MR (2010)
AIMS: To confirm and extend to primary care settings prior genome-wide association results that distinguish smokers who successfully quit from individuals who were not able to quit smoking in clinical trials. MATERIALS and METHODS: Affymetrix 6.0 Arrays were used to study DNA from successful quitters and matched individuals who did not quit from the Patch in Practice study of 925 smokers in 26 UK general practices who were provided with 15 mg/16 h nicotine-replacement therapy and varying degrees of behavioral support. RESULTS: Only a few SNPs provided results near 'genome-wide' levels of significance. Nominally significant (p < 0.01) SNP results identify the same chromosomal regions identified by prior genome-wide association studies to a much greater extent than expected by chance. CONCLUSION: Ability to change smoking behavior in a general practice setting appears to share substantial underlying genetics with the ability to change this behavior in clinical trials, though the modest sample sizes available for these studies provides some caution to these conclusions.